2014
DOI: 10.3390/molecules19044301
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive 30-Noroleanane Triterpenes from the Pericarps of Akebia trifoliata

Abstract: Abstract:Two new 30-noroleanane triterpenes, 2α,3β,20α-trihydroxy-30-norolean-12-en-28-oic acid (1), 2α,3β-dihydroxy-23-oxo-30-norolean-12,20(29)-dien-28-oic acid (2), were isolated from the pericarps of Akebia trifoliata, together with four known ones, 3β-akebonoic acid (3), 2α,3β-dihydroxy-30-noroleana-12,20(29)-dien-28-oic acid (4), 3α-akebonoic acid (5) and quinatic acid (6). Their structures were established on the basis of detailed spectroscopic analysis, and they were all isolated from the pericarps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…Only compound 5 showed interesting cytotoxicity against HCT-116, HepG2 and SGC-7901 cell lines, with IC 50 values of 9.1, 15.2 and 41.0 µM, respectively. Previous cytotoxicity studies on this type of nortriterpenoids suggested that the exocyclic double bond at C-20(29) might be an important active center to "maintain" their potential cytotoxicity [5], while the present result suggested that the saccharide unit attached at C-28 could greatly reduce the in vitro cytotoxicity. …”
Section: Cytotoxicity Assaycontrasting
confidence: 51%
See 1 more Smart Citation
“…Only compound 5 showed interesting cytotoxicity against HCT-116, HepG2 and SGC-7901 cell lines, with IC 50 values of 9.1, 15.2 and 41.0 µM, respectively. Previous cytotoxicity studies on this type of nortriterpenoids suggested that the exocyclic double bond at C-20(29) might be an important active center to "maintain" their potential cytotoxicity [5], while the present result suggested that the saccharide unit attached at C-28 could greatly reduce the in vitro cytotoxicity. …”
Section: Cytotoxicity Assaycontrasting
confidence: 51%
“…Recently, a phytochemical study revealed six triterpenoid saponins, including two noroleanane-type ones from a methanol extract of root of H. coriacea [2]. Noroleanane triterpenoids are recognized as characteristic constituents of the family Lardizabalaceae, some of which were revealed to show significant bioactivities [3][4][5]. Our interest in the chemistry of noroleanane triterpenoids prompted us to continue the phytochemical study of H. coriacea, whereby three new 30-noroleanane triterpenoid saponins (1-3) and five known ones (4)(5)(6)(7)(8) were obtained from the stem of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of chemical composition, published literature about AF has mainly focused on the separation and extraction of chemical components. Versatile botanical secondary metabolites of AF, including triterpenoids, triterpenoid saponins, phenylethanoid glycosides, coumarins, iridoids and essential oils, have been isolated by phytochemical approaches . Currently, few reports are focused on the systematic characterization of the chemical constituents from AF, and only a few compounds have been identified .…”
Section: Introductionmentioning
confidence: 99%
“…Versatile botanical secondary metabolites of AF, including triterpenoids, triterpenoid saponins, phenylethanoid glycosides, coumarins, iridoids and essential oils, have been isolated by phytochemical approaches. [22][23][24][25][26] Currently, few reports are focused on the systematic characterization of the chemical constituents from AF, and only a few compounds have been identified. 27,28 In addition, as a TCM, AF has been widely used in the Herein, we propose a UPLC/QTOF-MS E analysis coupled with a four-step strategy for comprehensive profiling of the main compounds of AF.…”
mentioning
confidence: 99%
“…Phytochemical investigation has found that A. trifoliata contains many constituents including triterpenes (Wang et al, ; Wang et al, ), triterpenoid saponins (Gao & Wang, ; Gao & Wang, ; Matsuzaki, Murano, Endo, & Kitanaka, ; Mimaki et al, ; Wang, Lu, & Lin, ; Xu et al, ), lignan glycosides (Guan et al, ), phenylpropanoids (Wang, Zhou, Xu, & Tan, ) and caffeoylquinic acid derivatives (Wang, Xu, Zhou, & Tan, ). Among them, the triterpenoid saponins are the main bioactive constituents which contribute to the diuretic pharmacological activity of A. trifoliata .…”
Section: Introductionmentioning
confidence: 99%